Study of cervical lymphadenopathy - Rajiv B. Jadhav; N. Vijay; M.D. Sharik (Al Ameen Medical College, 2019)
Background: Cervical lymphadenopathy is commonly seen in surgical practice. This study is aimed to study causes of cervical lymphadenopathy, age group of involment, group of lymph node involment and characteristic of involed lymph node. Method: Carried out by prospectively collected 78 cases of chronic cervical lymphadenopathy from the Department of General Surgery. Results: Tuberculous adenitis is the common cause of cervical lymphadenitis with70% cases followed by chronic non-specific lymphadenitis with 15% cases, lymphoma with 5% cases, secondary carcinoma with 5% cases and drug induced 5%,there were 46% males and 54% females Most of the patients belong to the poor socio-economical class and commonest presenting symptom was swelling in the neck, unilateral lymph node involvement was seen in 90%,upper anterior deep cervical lymph node 46% followed by Sub-mandibular and sub- mental nodal involvement 26%cases were seen. Conclusion: Tuberculous adenitis is most common cause of cervical lymphadenopathy usually present as unilateral lymph nodes enlargement without constitutional symptoms upper and anterior deep cervical followed by sub-mandibular and sub-mental commonly involed lymph node.